Assessing The Impact of Habitat Loss and Human Development on Proboscis Monkey Distribution in South Kalimantan - Abdi Fithria; Rina Kanti; Arfa Agustina Rezekiah; Syam'ani; Yasinta Nur Shiba (UIN Sunan Gunung Djati Bandung, 2025)
The proboscis monkey (Nasalis larvatus) is an endemic primate species of Borneo that plays a crucial role in maintaining the health of riparian forest ecosystems. However, habitat loss due to deforestation, land conversion, and urbanization has led to significant population declines. This study aims to analyze the habitat characteristics and dispersal patterns of the proboscis monkey in the riparian zone of the Tabunio Watershed, South Kalimantan, Indonesia. Geospatial modeling techniques, including Kernel Density Analysis (KDA) and spatial regression, were employed to assess habitat suitability and predict species dispersal. Sentinel-2 multispectral imagery from 2018, 2019, and 2021 was utilized to extract vegetation biophysical parameters, such as Leaf Area Index (LAI), Canopy Chlorophyll Content (CCC), and Fraction of Vegetation Cover (FVC), which were integrated with field survey data. The results indicate a significant correlation between the distribution of proboscis monkeys and vegetation health, with dense riparian vegetation providing optimal habitat conditions for these monkeys. The findings also highlight the adverse impact of human-induced changes in land cover on populations of the proboscis monkey. Conservation measures, including habitat restoration and the establishment of protected areas, are recommended to mitigate habitat fragmentation and ensure the long-term survival of the species. This study contributes to the understanding of habitat dynamics and provides valuable insights for the sustainable management of riparian ecosystems in South Kalimantan